Tell Me About Your Visit With the Lions: Eliciting Event Narratives to Examine Children’s Memory and Learning During Summer Camp at a Local Zoo - Kian, Tida; Parmar, Puneet K.; Fabiano, Giulia F.; Pathman, Thanujeni (Frontiers in Psychology, 2021)
School-aged children often participate in school field trips, summer camps or visits at informal learning institutions like zoos and museums. However, relatively little is known about children’s memory and learning from these experiences, what types of event details and facts are retained, how retention varies across age, and whether different patterns are observed for different types of experiences. We aimed to answer these questions through a partnership with a local zoo. Four- to- 10-year-old children (N=122) participated in a weeklong summer camp, where they engaged in dynamic events, including visits to zoo animals. On the last day of camp, we elicited autobiographical event narratives for two types of experiences: a child-selected event (visit to their favourite animal) and an experimenter-selected animal event. We coded event narratives for length and breadth using previously used autobiographical memory narrative coding schemes. In addition, we created a coding scheme to examine retention of semantic information (facts). We report the types of autobiographical event details and facts children recalled in their narratives, as well as age group differences that were found to vary depending on the type of information and type of event. Through this naturalistic, yet controlled, study we gain insights into how children remember and learn through hands-on activities and exploration in this engaging and dynamic environment. We discuss how our results provide novel information that can be used by informal learning institutions to promote children’s memory and retention of science facts.